A new species of Liolaemus (Reptilia: Squamata) of the Liolaemus capillitas clade (Squamata, Liolaemini, Liolaemus elongatus-kriegi group) from Sierra de Velasco, La Rioja Province, Argentina - Avila, Luciano Javier; Vrdoljak, Juan Esteban; Medina, Cintia Débora; Massini, Juan García; Perez, Cristian Hernán Fulvio; Sites, Jack W. Jr.; Morando, Mariana (Zootaxa, 2021)
A new species of the Liolaemus capillitas clade is described. Liolaemus galactostictos sp. nov. differs from other members of its group by a combination of morphological and molecular traits, in particular its black dorsal coloration pattern not found in any other Liolaemus species. Liolaemus galactostictos sp. nov. is only known from its type locality. This new species is found in rocky fields surrounded by grasslands on the top of the Velasco Mountains, a ¨sky island environment¨, in northwestern Argentina. As well as other members of its clade this species seems to be strictly saxicolous, viviparous and feeds on insects.